PERENCANAAN METODE PELAKSANAAN DAN RENCANA ANGGARAN BIAYA REKONSTRUKSI JPO PASAR MINGGU - Naomi Oktriani Br Damanik; Kusno Adi Sambowo (Jurnal Infrastruktur, 2018)
The crossing bridge at Pasar Minggu is the link between the train station and the shopping center opposite. The reconstruction of the collapsed bridge starts with problem identification and research, then chooses the most appropriate method to use in the reconstruction process, and calculates the cost for the reconstruction of the bridge. From the research results it can be seen that the bridge is reconstructed by retrofitting method where the existing bridge structure is reinforced by the method of scaffolding and launching, so that the bridge is again become feasible to be used, and the cost required to reconstruct the bridge is Rp 1.213.239.230.